2019
DOI: 10.1002/lpor.201900165
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Hyperspectral Data with Colloidal Quantum Dots

Abstract: Hyperspectral sensors, combining the functions of photon detection with ultrahigh spectral resolution in a single device, have emerged as a new class of devices with significant potential for applications that rely on the input of optical information. Despite continued advancement, the widespread use of infrared hyperspectral sensors is still limited primarily due to the high cost associated with the growth and processing of epitaxial semiconductors, such as HgCdTe, InSb, and superlattices. Here, it is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 46 publications
(61 reference statements)
0
64
0
Order By: Relevance
“…Then, we will focus on -c) Reproduced with permission. [85] Copyright 2019, Wiley-VCH. d) The schematic of the on-chip detection with the plasmonic-silicon hybrid waveguide system with the inset of the cross-section of the metal-insulatormetal (MIM) waveguide with HgTe QD coating (left).…”
Section: Color Conversion and Lasingmentioning
confidence: 99%
“…Then, we will focus on -c) Reproduced with permission. [85] Copyright 2019, Wiley-VCH. d) The schematic of the on-chip detection with the plasmonic-silicon hybrid waveguide system with the inset of the cross-section of the metal-insulatormetal (MIM) waveguide with HgTe QD coating (left).…”
Section: Color Conversion and Lasingmentioning
confidence: 99%
“…Besides enhancing absorption, optical structures can also be used for better spectral resolution. By combining HgTe CQD photovoltaic sensors with distributed Bragg mirror filter array in a single device, Tang et al, reported a CQDs hyperspectral sensor [57], which realized acquisition of hyperspectral data with 64 narrowband channels and full-width at half-maxima down to 30 cm −1 , as shown in Figure 3h. Coatings 2020, 10, x FOR PEER REVIEW 6 of 14 In order to better reflect the development of infrared CQDs photodetectors, Table 1 shows the performance comparison between HgTe CQDs photodetectors over the past decade.…”
Section: Infrared Cqds Photodetectorsmentioning
confidence: 99%
“…Efficient detection of photons lies at the heart of several modern technologies. [ 1 ] Although specialized high‐sensitivity detectors for specific wavelength ranges exist, [ 2–6 ] of late, there has been significant interest for the development of broadband photodetectors (PDs) for hyperspectral sensing. [ 7–12 ] Sensing over a very broad wavelength range is potentially very important for imaging applications, since it can enable for the identification of multiple parameters including morphology, temperature, chemical composition, etc.…”
Section: Introductionmentioning
confidence: 99%